Bilingualism in Down Syndrome: A Greek Study. Issue 3 (4th May 2021) - Katsarou, Dimitra; Andreou, Georgia
ABSTRACT: Children with Down syndrome (DS) present language deficits in all linguistic domains and their language development lags behind that of typically developing children. However, their receptive language skills appear to be better than their productive in all linguistic domains. Research on bilingual children with DS is limited, but has shown that second language learning from an early age by children with DS has no impact on their first language development. In this research study, we examined receptive and productive first language skills of eight monolingual and eight bilingual children with DS. For the above purpose, a standardised language test, that measures the receptive and expressive language system, was administered to all participants. The results of our study showed that bilingual children with DS do not differ in their receptive and productive language skills from monolingual children with DS, indicating that bilingualism does not affect first language development in DS.